Falcon synergy tech: FlexDry PortaRack / Iman Nabila Mohazam Shah … [et al.] - Mohazam Shah, Iman Nabila; Mohd Khairil, Nur Aliya Adlina; Rosli, Nur Raimi Batrisyia; Tahir, Nur Syafiqah; Kamaroulzaman, Nuraisyah Fasiha (2023)
The FlexDry PortaRack is a modern portable clothes dryer that was created to solve the problems that contemporary travelers encounter while trying to dry their garments quickly while on the road. Convenience, usefulness, and hygiene maintenance are the goals of this creative approach, which does not rely on costly washing facilities or conventional air-drying techniques. A thorough methodology was used in the development of the FlexDry PortaRack, which included market research and analysis, target audience definition, conceptualization and design, prototyping, technical development, adherence to standards, manufacturing, marketing, and branding, distribution and sales, and ongoing improvement based on user input and industry trends. The product addresses the inefficiency of traditional drying methods, limited access to laundry facilities, and the energy inefficiency of existing portable dryers. Through observation, surveys, and extensive research, the team identified the specific needs and preferences of travelers, leading to the creation of a compact, lightweight, and energy-efficient clothes dryer that fits well within the constraints of travel. The FlexDry PortaRack not only provides a practical and hygienic solution for travelers but also fills a significant market gap. Its incremental enhancements and increased value within the current product market make it a compelling choice for individuals seeking a reliable and convenient solution for drying their clothes while on the move. The FlexDry PortaRack will completely transform the way travellers maintain hygiene and cleanliness while travelling, with an intense focus on customer input, ongoing improvement, and compliance with safety and regulatory requirements.